2020
DOI: 10.31234/osf.io/wfdhx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dying to divulge: The determinants of, and relationship between, desired and actual disclosure

Abstract: Studies suggest that sharing thoughts and information with others may be inherently pleasurable and confer health, psychological, and social benefits to the discloser. At the same time, self-disclosure exposes individuals to scrutiny and the risk of rejection and reputational damage, particularly with the advent of digital applications and social media outlets that promote public, and often permanent, disclosing. In an effort to understand the tradeoffs that underlie the decision to disclose, we introduce a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Although the studies reported in Carbone and Loewenstein (2020) provide a range of insights about the desire to share information, perhaps the most relevant to the current paper is a finding regarding reasons for sharing. In that study, respondents to a survey ( n = 552) were asked an open‐ended question about whether they could recall a situation in which they were “dying to share” information with another person; then, if they could recall such a situation, whether they had ended up sharing the information, as well as a series of follow‐up questions about what information they were dying to share and who they were dying to share it with.…”
Section: Can Individuals Effectively Manage Privacy Online?mentioning
confidence: 98%
See 1 more Smart Citation
“…Although the studies reported in Carbone and Loewenstein (2020) provide a range of insights about the desire to share information, perhaps the most relevant to the current paper is a finding regarding reasons for sharing. In that study, respondents to a survey ( n = 552) were asked an open‐ended question about whether they could recall a situation in which they were “dying to share” information with another person; then, if they could recall such a situation, whether they had ended up sharing the information, as well as a series of follow‐up questions about what information they were dying to share and who they were dying to share it with.…”
Section: Can Individuals Effectively Manage Privacy Online?mentioning
confidence: 98%
“…While much of the literature on privacy tends to focus on the risks of information leakage, those concerned about privacy need to contend with the fact that in most situations privacy‐related motivations are counterpoised against potentially even stronger motives for socializing, connecting, and sharing information. Individuals have many reasons for sharing information, including economic benefits that result from strategic revelation or withholding, and an array of psychological motives (Carbone & Loewenstein, 2020). One study using subjective measures as well as fMRI (Tamir & Mitchell, 2012) found that information sharing is inherently pleasurable, particularly when the information relates to one's own thoughts and feelings.…”
Section: Can Individuals Effectively Manage Privacy Online?mentioning
confidence: 99%
“…Consistent with impression management as a driver of disclosure, people are generally more inclined to disclose positively (vs. negatively) valenced personal information (Berman et al., 1988; Carbone & Loewenstein, 2020). For instance, Waterloo et al.…”
Section: Active Disclosurementioning
confidence: 98%
“…The prevailing explanation for confessions is that decision makers rationally weigh these costs against the benefits of disclosing. Although benefits can take the material form of experiential information—for instance, practical information about strategies, resources, and general “know‐how” from those with similar lived experiences (Borkman, 1999)—confessions often occur with little or no expectation of a useful, supportive response from the recipient of the information, or indeed any response at all: Our own work on confessions reveals that the vast majority (87%) of survey participants who made anonymous online confessions ( N = 195) did so at least in part to “vent” or achieve emotional release, and participants' self‐reported improvement in emotional and psychological state after confessing was virtually unaffected by whether or not they received feedback from others on the platform (Carbone et al, 2022). True, just as breaking a diet does bring pleasure from indulging or practicing unintended unsafe sex can be momentarily gratifying, confessing may result in psychological benefits, such as an “unburdening” of the pressure of concealment.…”
Section: The Drive To Disclosementioning
confidence: 99%
“…Our own unpublished work takes such investigation a step further by attempting to document experiences of a visceral desire to disclose and quantify this experience (Carbone & Loewenstein, 2020). Asked whether they had ever felt like they were “dying” to tell someone something, the overwhelming majority (79%) of study participants ( N = 215) indicated that they had indeed experienced such an intense desire to disclose in the past.…”
Section: The Drive To Disclosementioning
confidence: 99%